Is the local wheat market a 'market for lemons'? Certifying the supply of individual wheat farmers in Ethiopia. (8th April 2021) - Anissa, Banawe Plambou; Abate, Gashaw; Bernard, Tanguy; Bulte, Erwin
Abstract: Bulking and mixing of smallholder supply dilutes incentives to supply high quality. We introduce wheat 'grading and certification shops' in Ethiopia and use an auction design to gauge willingness-to-pay (WTP) for certification. Bids correlate positively with wheat quality, and ex ante notification of the opportunity of certification improves wheat quality. These findings suggest that local wheat markets resemble a 'market for lemons', crippled by asymmetric information. However, aggregate WTP for grading and certification services does not re-coup the sum of fixed, flow and variable costs associated with running a single certification shop.